Gypsum scale formation on graphene oxide modified reverse osmosis membrane - Bo Cao; Ali Ansari; Xinyi Yi; Rodrigues, Debora F*.; Yandi* Hu (Journal of Membrane Science, 2018)
Graphene oxide (GO) coatings on membranes can improve antifouling performance against a variety of microorganisms and organics. However, the effects of GO coatings on mineral scaling were not investigated. Here gypsum scaling on bare (ESPA2) and GO-modified thin-film polyamide membranes (ESPA2-GO) followed by cleaning with deionized (DI) water were investigated with a bench-scale reverse osmosis setup. The flux decline caused by gypsum scaling on ESPA2-GO was slightly reduced than on ESPA2. This is because the ESPA2-GO membrane is more hydrophilic than ESPA2, indicating a higher energy barrier for heterogeneous nucleation and/or the deposition of gypsum on it. Moreover, the more negatively charged ESPA2-GO membrane lead to stronger electrostatic repulsive forces between the membrane and the negatively charged gypsum particles and thus further inhibiting gypsum deposition onto membranes. Interestingly, during the cleaning process, smaller flux recovery was observed for ESPA2-GO. This is because ESPA2-GO surfaces have higher densities of carboxyl (–COOH) groups, which form complexes with Ca2+, building strong bonds between GO coatings and gypsum. This study provided unique insights on the physicochemical interactions among membrane, the scaling mineral, and aqueous species, which can help the rational design of coatings for better simultaneous anti-scaling and anti-fouling performances.
Keywords: Graphene oxide coating; Gypsum scaling; Heterogeneous nucleation and deposition; Polyamide membranes; Reverse osmosis